Risk assessment of Oropouche virus transmission by mosquitoes in Europe - Jansen, Stephanie; Lühken, Renke; Höller, Patrick; Mack, Amrei; Lange, Unchana; Jöst, Hanna; Becker, Norbert; Heitmann, Anna (The journal of infectious diseases, 2025)
Oropouche virus (OROV) emerged as a significant health threat in Central and South America in 2024. Culicoides (Diptera: Ceratopogonidae) is considered the primary vector, while the role of mosquitoes in the transmission cycle is still unclear. This study evaluates the vector competence of 5 mosquito species common in Europe for OROV (old strain). While Culex torrentium, Culex pipiens biotype pipiens, Aedes aegypti, and Aedes japonicus showed no transmission, Aedes albopictus demonstrated low transmission at higher temperatures. Temperature-based risk analysis for areas with established A albopictus populations suggests that regions around the Mediterranean are at potential risk for OROV transmission.